Short Communication: Morpho-palynological study of the endemic species Sarcopyramis subramanii (Melastomataceae) from Northeast India - BARNALI DAS; NAMITA NATH (Society for Indonesian Biodiversity, 2026)
Abstract. Das B, Nath N. 2026. Short Communication: Morpho-palynological study of the endemic species Sarcopyramis subramanii (Melastomataceae) from Northeast India. Biodiversitas 27 (1): d270105. https://doi.org/10.13057/biodiv/d270105. The family Melastomataceae is known for its diplostemonous flowers and appendaged anther connectives. Sarcopyramis is a very small genus within this family with only four accepted taxa across the world. The structure of the calyx apex plays a vital role in differentiating the taxa under this genus. Sarcopyramis subramanii is an endemic plant from northeast India, and has not been studied in detail. This plant was misidentified as S. napalensis, a morphologically similar plant, for a long time. This study aimed to analyze the detailed taxonomic aspects along with palynological features using SEM microscopy to facilitate the adequate identification of this lesser-known species. Plant samples have been collected from three different locations in Assam, northeast India. Photographs of habit, floral parts, and SEM images of pollens are included here for proper validation. The pollen of S. subramanii is prolate-spheroidal in shape with colporate and colpate apertures. From the palynological data, these two species can be easily distinguished as the pollens of S. subramanii possess an outgrowth structure in the colpi. The P/E ratio of S. subramanii is 1.06, whereas S. napalensis is 1.63. The plant should be conserved due to the ongoing rapid habitat destruction, as it has a limited geographical range and a very small population.